Protocol for mapping 2′-O-methylation using nanopore direct RNA-seq data with NanoNm - Yanqiang Li; Jiayi Chen; Yunxia Wang; Dean Li; Jiahan Li; Yang Yi; Lili Zhang; Qi Cao; Kaifu Chen (STAR Protocols)
Summary: 2'-O-methylation (Nm) is pivotal in rRNA and the internal site of mRNA. Here, we present an integrated bioinformatics protocol for the identification of 2′-O-methylation using nanopore direct RNA sequencing (RNA-seq) data. We describe steps for software installation, data collection, and training the machine learning model. We then detail procedures for mapping 2′-O-methylation in both rRNA and mRNA in yeast and human cells.For complete details on the use and execution of this protocol, please refer to Li et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.